2023
DOI: 10.3390/medicina59112002
|View full text |Cite
|
Sign up to set email alerts
|

Association of the HALP Score with Dyslipidemia: A Large, Nationwide Retrospective Study

Yazeed Alshuweishi,
Ahmed M. Basudan,
Mohammed Alfaifi
et al.

Abstract: Background and Objectives: Dyslipidemia is a major risk factor for cardiovascular disease (CVD). The identification of new biomarkers that may enhance the risk assessment of lipid abnormalities is a promising approach in improving risk prediction of CVD. There is no information on the association of the hemoglobin, albumin, lymphocyte, and platelet (HALP) score with dyslipidemia. The aim of this study was to investigate the clinical utility of the HALP score in light of dyslipidemia. Materials and Methods: A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Recently, much clinical research suggested that a low HALP score was indicative of a poor prognosis in multiple tumors (17)(18)(19)(20). The latest studies have suggested that the HALP score is also related to dyslipidemia (21), which is a commonly acknowledged risk factor for DR. Nevertheless, the available evidence concerning the association between the HALP score and the occurrence of DR is extremely restricted.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much clinical research suggested that a low HALP score was indicative of a poor prognosis in multiple tumors (17)(18)(19)(20). The latest studies have suggested that the HALP score is also related to dyslipidemia (21), which is a commonly acknowledged risk factor for DR. Nevertheless, the available evidence concerning the association between the HALP score and the occurrence of DR is extremely restricted.…”
Section: Introductionmentioning
confidence: 99%